2003
DOI: 10.1046/j.1470-6431.2003.00297.x
|View full text |Cite
|
Sign up to set email alerts
|

Consumer socialization, social structural factors and decision‐making styles: a case study of adolescents in Malaysia

Abstract: The purpose of this study is to investigate how the process of consumer socialization will determine adolescents’ decision‐making styles. Eight decision‐making styles were conceptualized as outcomes of the socialization process, which is acquired via interaction with socialization agents, namely parents, peers, printed media, television commercials and in‐school education. The study also proposed five social structural variables (social class, gender, ethnicity, residence and religion) as being associated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
116
0
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(125 citation statements)
references
References 19 publications
5
116
0
4
Order By: Relevance
“…In addition, 33% of the students show personal preferences for expensive clothes and accessories and more than 40% believe that money is the most important factor in life (Sorrooshian & Teck, 2014). The obtained data are in accordance with the study by Kamaruddin and Mokhlis (2003), which indicates that the largest proportion of everyday spending of Malaysian teenagers is on clothes, makeup, food, athletic equipment and entertainment. This goes in the same direction with the research done by Ahmed, Ghingold and Zainurin (2007), who studied Malaysian teenagers' attitudes towards product consumption.…”
Section: Groups 2013)supporting
confidence: 88%
“…In addition, 33% of the students show personal preferences for expensive clothes and accessories and more than 40% believe that money is the most important factor in life (Sorrooshian & Teck, 2014). The obtained data are in accordance with the study by Kamaruddin and Mokhlis (2003), which indicates that the largest proportion of everyday spending of Malaysian teenagers is on clothes, makeup, food, athletic equipment and entertainment. This goes in the same direction with the research done by Ahmed, Ghingold and Zainurin (2007), who studied Malaysian teenagers' attitudes towards product consumption.…”
Section: Groups 2013)supporting
confidence: 88%
“…One of the reasons peers are able to influence purchasing decisions emanate from the fact that some young adults often feel less confident to evaluate their buying decisions, and would rather rely on their peers to enhance this process. In another study, peers emerged as the most important reference group in a purchase decision process (Kamaruddin & Mokhlis, 2003), consistent with the findings of Yoh (2005). In addition, the importance of peers is reinforced by the findings of Khan and Khan (2005), which concluded that friends tend to be dominant informational reference group.…”
Section: Peerssupporting
confidence: 69%
“…Therefore, it is critical for marketers and managers in charge of designer labels' to focus on the avenues and approaches to prioritize these factors to enhance the success of their marketing campaign to attract young adults in Malaysia. In contrast, previous studies revealed that peers influence tend to be considered as the most important factor in the decision to purchase designer label apparels (Kamaruddin & Mokhlis, 2003;Yoh, 2005). The industry, therefore, should take into account the findings in this study in order to ensure that they gain some insights about the dynamics of the key factors to consider within the designer label apparels market in Malaysia.…”
Section: Discussion and Research Implicationsmentioning
confidence: 77%
“…As the standard of living in Malaysia has improved significantly and stimulated changing lifestyles, college students today are granted greater freedom from their parents to make their own shopping and consumption decisions (Kamaruddin & Mokhlis, 2003). Based on this finding, the student must have an adequate financial knowledge in order to make the best possible decisions financially or if not, this will result in a conspicuous consumption and will further lead to poor financial management.…”
Section: Introductionmentioning
confidence: 99%